2020
DOI: 10.20944/preprints202010.0158.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying Sugarcane Response to Aluminum Stress by RNA-Seq

Abstract: Sugarcane is an important sugar-source crop. As any other plant, it can be exposed to several abiotic stress conditions. Though some metals contribute to critical physiological processes in plants, the presence of aluminum ions (Al3+) can be very toxic. In order to develop plants that flourish in acidic soils, it is critical to gain insights into the molecular mechanisms of sugarcane response to aluminum stress. To determine the genes involved in sugarcane response to aluminum stress we generated 372 million p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…5C ). Recently, Rosa-Santos et al (2020) reported in (Al-sensitive) and CTC-2 (Al-tolerant) cultivars that genes related to the auxin signaling, detoxification, ROS protection, and signal transduction were significantly involved in sugarcane response roots to Al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5C ). Recently, Rosa-Santos et al (2020) reported in (Al-sensitive) and CTC-2 (Al-tolerant) cultivars that genes related to the auxin signaling, detoxification, ROS protection, and signal transduction were significantly involved in sugarcane response roots to Al.…”
Section: Discussionmentioning
confidence: 99%
“…Differentially regulated genes have been identified in two sugarcane cultivars with more than 4,000 differentially expressed genes (DEGs) in the tolerant cultivar and only about 850 DEGs in the Al sensitive cultivar. Among several transcripts, the ARF ( Auxin responds factor ), MT1 ( metallothionein-like protein 1), CDPK ( calcium-dependent protein kinase ), and Glutathione S-transferases genes were substantially active in Al tolerance mechanisms; ARF was related to auxin signaling, MTI to detoxification, CDPK to signal transduction, and Glutathione S-transferases it ROS protection mechanism ( Rosa-Santos et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, transcriptional expression with RNA sequencing techniques has been used to study Al toxicity tolerance mechanisms in other crops such as sugarcane 29 , buckwheat 30 , and tea plants 31 , allowing the identification of new genes involved in the response to this abiotic stress. The investigation of Al-responsive genes in maize has focused mostly on the early developmental stages and using a microarray approach.…”
Section: Introductionmentioning
confidence: 99%